Role of Platelets in Rheumatic Chronic Autoimmune Inflammatory Diseases - Péč, Martin Jozef; Jurica, Jakub; Péčová, Monika; Benko, Jakub; Sokol, Juraj; Bolek, Tomáš; Samec, Marek; Hurtová, Tatiana; Galajda, Peter; Samoš, Matej; Mokáň, Marián (Seminars in Thrombosis and Hemostasis, 2023)
Platelets are essential in maintaining blood homeostasis and regulating several inflammatory processes. They constantly interact with immune cells, have immunoregulatory functions, and can affect, through immunologically active substances, endothelium, leukocytes, and other immune response components. In reverse, inflammatory and immune processes can activate platelets, which might be significant in autoimmune disease progression and arising complications. Thus, considering this interplay, targeting platelet activity may represent a new approach to treatment of autoimmune diseases. This review aims to highlight the role of platelets in the pathogenic mechanisms of the most frequent chronic autoimmune inflammatory diseases to identify gaps in current knowledge and to provide potential new targets for medical interventions.
Keywords: psoriasis; systemic sclerosis; systemic lupus erythematosus; chronic inflammatory arthritis